Measurement of soil electrical conductivity based on direct digital synthesizer (DDS) and digital oscilloscope - Pei, Xiaoshuai; Meng, Chao; Li, Minzan; Yang, Wei; Zhou, Peng (International Journal of Agricultural and Biological Engineering, 2019)
A soil electrical conductivity (EC) measurement system based on direct digital synthesizer (DDS) and digital oscilloscope was developed. The system took the “current-voltage four-electrode method” as the design principal and adopted a six-pin structure of the probe, two center pins to measure the soil EC in shallow layer, two outside pins to measure the soil EC in deep layer, and two middle pins for inputting the driving current. A signal generating circuit using DDS technology was adopted to generate sine signals, which was connected with the two middle pins. A digital oscilloscope was used to record and store the two soil output signals with noises in microseconds, which were from the two center pins and two outside pins, respectively. Then a digital bandpass filter was used to filter the soil output signals recorded by the digital oscilloscope. Compared with the traditional analog filter circuit, the digital filter could filter out the noises of all frequency except for the frequency of the excitation source. It could improve the effect of filtering and the accuracy of the soil EC measurement system. The DDS circuit could provide more stable sine signals with larger amplitudes. The use of digital oscilloscope enables us to analyze the soil output signals in microseconds and measure the soil EC more accurately. The new soil EC measurement system based on DDS and digital oscilloscope can provide a new effective tool for soil sensing in precision agriculture.Keywords: soil electrical conductivity, direct digital synthesizer, digital oscilloscope, precision agriculture, current-voltage four-electrode methodDOI: 10.25165/j.ijabe.20191206.4840Citation: Pei X S, Meng C, Li M Z, Yang W, Zhou P. Measurement of soil electrical conductivity based on direct digital synthesizer (DDS) and digital oscilloscope. Int J Agric & Biol Eng, 2019; 12(6): 162–168.